The Influence Of Entrepreneurial Competence And The Utilization Of Digital Marketing To Improve Business Performance In The Community Of Weru Kidul Village, Weru District, Cirebon District - Erna Erna; Ekarat Chaichotchuang; R Misriah Ariyani; Vita Dhameria; Mahmud Mahmud; Bambang Hermani (Jurnal Telekomunikasi dan Informatika, 2024)
Weru Kidul Village has several industrial potentials, including the handicraft industry, food industry, materials industry, savings and loan cooperatives, restaurants, and livestock. Based on the data from BPS, the number of entrepreneurs in Indonesia is only 3.47%, which still needs to be increased to become a developed country. Indonesia needs 12 to 14 percent. In this case, an increase in entrepreneurs needs to increase the number of entrepreneurs in Indonesia. This study aims to determine how much influence entrepreneurial competency and digital marketing use have on business performance. The method used in this research is a quantitative descriptive method. From the results of the study, it was found that entrepreneurial competence and the use of digital marketing had a significant effect on business performance.